Method For Determining the Qiblat Direction of The Mosque: Analysis of Determining the Qibla Direction of the Al-Islahiyah Mosque, Gampong Lambhuk, Ulee Kareng District, Banda Aceh City - Aindana Zulfa; Riza Afrian Mustaqim (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
Some village officials want to adjust the direction of the Qibla, but some Gampong residents oppose the plan because residents believe that the direction of the Qibla has been determined by previous generations of scholars. This study will investigate the approach used when the determination of the direction of the Qibla was first carried out, as well as the approach used after the revision in 2017. Qualitative field research (field research) and library research (library research) used descriptive, analytical, and verification approaches. After that, the method of determining the direction of the Qibla of the Al-Ishlahiyah Mosque was described and analyzed. Furthermore, the results of the re-measurement of the current direction of the Qibla were verified using the Compass and Rasdul Qibla/Istiwa A’zam. The results show that first, the direction of the Qibla was determined at the Al-Ishlahiyah Mosque using two methods: Rasdul Qibla/Istiwa A’zam on May 28, 2015 and the Compass tool in 2017. In 1966, the direction of the Qibla was determined with a tool perpendicular to the shadow of the sun's rays before it became a Mosque and was still a Meunasah Gampong. Second, the analysis of the current Qibla direction determination method is appropriate, by following the Compass of the Baiturrahman Grand Mosque in Banda Aceh at point 292o and Rasdul Qiblat/Istiwa A'zam on May 27, 2022 at 16:18 WIB and July 16, 2022 at 16:30 WIB. The calibration results show a slight slope of 11o.